2011
DOI: 10.1128/aem.00047-11
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Transcriptional and Physiological Responses of Bradyrhizobium japonicum to Paraquat-Mediated Oxidative Stress

Abstract: The rhizobial bacterium Bradyrhizobium japonicum functions as a nitrogen-fixing symbiont of the soybean plant (Glycine max). Plants are capable of producing an oxidative burst, a rapid proliferation of reactive oxygen species (ROS), as a defense mechanism against pathogenic and symbiotic bacteria. Therefore, B. japonicum must be able to resist such a defense mechanism to initiate nodulation. In this study, paraquat, a known superoxide radical-inducing agent, was used to investigate this response. Genome-wide t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 64 publications
1
25
0
4
Order By: Relevance
“…In the particular example of B. diazoefficiens, the respiration rate might be just such a signal linked to the transcription of the lateral-flagellar regulon. Previous reports indicated that situations diminishing the respiration rate, such as microaerobiosis, the bacteroid state (23), or iron deficiency (24), downregulate the lateral-flagellar regulon transcription, whereas situations known to increase the oxygen consumption, such as permanent exposure to moderate oxidative stress (25) or the use of arabinose as the sole carbon source (43; C. Cogo, J. Pérez-Giménez, C. B. Rajeswari, M. F. Luna, and A. R. Lodeiro, unpublished data), promote that transcription. Moreover, these changes in transcription were not observed in the subpolar-flagellar regulon, indicating that these stimuli act specifically on the lateral flagella.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the particular example of B. diazoefficiens, the respiration rate might be just such a signal linked to the transcription of the lateral-flagellar regulon. Previous reports indicated that situations diminishing the respiration rate, such as microaerobiosis, the bacteroid state (23), or iron deficiency (24), downregulate the lateral-flagellar regulon transcription, whereas situations known to increase the oxygen consumption, such as permanent exposure to moderate oxidative stress (25) or the use of arabinose as the sole carbon source (43; C. Cogo, J. Pérez-Giménez, C. B. Rajeswari, M. F. Luna, and A. R. Lodeiro, unpublished data), promote that transcription. Moreover, these changes in transcription were not observed in the subpolar-flagellar regulon, indicating that these stimuli act specifically on the lateral flagella.…”
Section: Discussionmentioning
confidence: 99%
“…Operon I contains flbT L , whose locus, upon activation, acts as a translation (Tln) inducer of the monocistronic lafA2 and appears to stabilize (Stb) the lafA1 transcript from a promoter within operon II. In addition to the effects of arabinose and mannitol, evidence from the literature indicates that prolonged exposure to moderate oxidative stress also induces lafR and the lateral flagellar regulon (25), whereas situations of O 2 limitation as the bacteroid state (23) or iron limitation (24) repress them. We also observed that viscosity and tortuousity of the medium induce lateral flagella (20) and that microoxia was reported as inhibiting lateral flagella genes expression (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B. japonicum strains were cultured in 20 ml of MMB glutamate or MMB glutamate plus ammonium to an OD 600 of 0.4 to 0.6. Cells were harvested and RNA was extracted as described previously (26)(27)(28). Synthesis of cDNA and quantitative reverse transcription-PCR (qRT-PCR) was performed using 3 g of total RNA as described previously (26)(27)(28).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were harvested and RNA was extracted as described previously (26)(27)(28). Synthesis of cDNA and quantitative reverse transcription-PCR (qRT-PCR) was performed using 3 g of total RNA as described previously (26)(27)(28). Data for three independent biological replicates were generated and normalized to the expression of the bll7457 gene, encoding the histidyl-tRNA synthetase HisS.…”
Section: Methodsmentioning
confidence: 99%